(untitled) (REMUNOM, 2024)
This study analyzes the social impacts of abortion legalization in Brazil, focusing on legal, cultural, and public health implications. The research addresses the historical evolution of Brazilian abortion laws, the religious and cultural influences on public debate, as well as the socioeconomic inequalities affecting access to safe abortion. The analysis explores the potential consequences of legalization in reducing unsafe abortions and easing the burden on the public health system, proposing an integrated approach to reproductive health policies. This study aims to contribute to a more balanced debate on women’s reproductive rights in Brazil, highlighting the urgency of policies that promote dignity, safety, and equity.